Железное кольцо: рассказы / Валентин Катаев - Катаев Валентин Петрович (Современник, 1989)
Экземпляры: ФИЛ (20110921) / Инвентарный номер: 949928 / Цена: 2.40 / Сис.шифр: Р2 / Авт.знак: К 29 / ГРНТИ: 17 / ББК: 84(2)